2010
DOI: 10.1029/2009jd013066
|View full text |Cite
|
Sign up to set email alerts
|

Return stroke peak current versus charge transfer in rocket‐triggered lightning

Abstract: [1] We examined data on 117 return strokes in 31 rocket-and-wire-triggered lightning flashes acquired during experiments conducted from 1999 through 2004 at the International Center for Lightning Research and Testing at Camp Blanding, Florida, in order to compare the peak currents of the lightning return strokes with the corresponding charges transferred during various time intervals within 1 ms after return stroke initiation. We find that the determination coefficient (R 2 ) for lightning return stroke peak c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…[] in a study of 143 RSs ( R 2 = 0.76) and by Schoene et al . [] in a study of 117 RSs, ( R 2 = 0.77). However, in their studies of TLFs in Shandong, China, Zhao et al .…”
Section: Statistics and Analysismentioning
confidence: 99%
“…[] in a study of 143 RSs ( R 2 = 0.76) and by Schoene et al . [] in a study of 117 RSs, ( R 2 = 0.77). However, in their studies of TLFs in Shandong, China, Zhao et al .…”
Section: Statistics and Analysismentioning
confidence: 99%
“…We note that triggered lightning return strokes are very similar, if not identical, to natural lightning subsequent strokes, strokes following the first stroke in natural lightning, with regard to measured current amplitudes and wave shapes [e.g., Fischer et al , ; Schoene et al , , ], and hence, the results found in this paper are likely applicable to strokes after the first stroke in natural lightning.…”
Section: Introductionmentioning
confidence: 99%
“…Rough estimates of peak current, subject to assumptions such as lightning channel geometry and return stroke speed [ Willett et al , 1989; Rachidi et al , 2004], are routinely provided by several nationwide lightning detection systems. Careful studies indicate that these two quantities are highly correlated in rocket‐triggered lightning on time scales of a few hundred microseconds after the return stroke, but this correlation drops with time indicating that the charge transfer at later time is not tightly linked to the return stroke peak current [ Schoene et al , 2010]. A further implication is that the lightning peak current is not necessarily relevant to the total charge transfer shortly after return strokes, which can be evaluated with the impulse charge moment change (iCMC, defined empirically as the product of charge transferred from cloud to ground within 2 ms after the return stroke and its original height above the ground) [ Cummer and Lyons , 2004, 2005].…”
Section: Introductionmentioning
confidence: 99%